EDM Molds a Smart Future.
While EDM is considered mature, the technology has gotten smarter in virtually every aspect. Built-in intelligence allows the machines, both wire and diesinker, to cut finer small and large molds. And using EDM in combination with high speed hard milling offers processing solutions for a variety of applications and industries, including automotive, consumer products and aircraft components.